Promoting Commodities through Comic Books: A Framing Analysis of the Captain Citrus Campaign - Tiffany M. Rogers; Joy N. Rumble; Lisa K. Lundy (Journal of Applied Communications, 2016)
The communication campaign starring Captain Citrus, first released in 2011, was aimed at elementary school students with the goals of encouraging health and agricultural literacy, as well as promoting the consumption of Florida orange juice. This study was designed as a qualitative, inductive framing analysis of the Captain Citrus comic book series featured in the campaign. The goal was to identify the prominent frames along with evidence of agricultural perspective and promotion throughout the series. The first two editions of the series, totaling 38 pages, were evaluated for the study. The results indicated the presence of four predominate frames: “Amazing Inside,” health, responsibility, and empowerment. A majority of the agricultural perspective and promotion was found in the form of images, followed by textual mentions, and symbolic references. It was determined that the “Amazing Inside” and health frames contributed to meeting the campaign objective to boost health literacy. The second objective, to promote agricultural literacy, was somewhat endorsed through the agricultural references, however there is an opportunity for this to be strengthened. The presence of all four frames aided in the achievement of the final goal, to promote Florida citrus through the sale of orange juice. It is recommended that further research be conducted to measure the effects of framing on the attitudes and behaviors of elementary school students before and after they are exposed to the campaign materials.
Keywords: Agricultural Literacy; Communication Campaign; Citrus; Content Analysis; Framing